2021
DOI: 10.1139/gen-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome-mediated epigenetic regulation of brain disorder and application of machine learning for multi-omics data analysis

Abstract: The gut-brain axis (GBA) is a biochemical link that connects the central nervous system (CNS) and enteric nervous system (ENS). Clinical and experimental evidence suggests gut microbiota as a key regulator of GBA. Microbes living in the gut, not only interact locally, with the intestinal cells and ENS, but have also been found to modulate CNS through neuroendocrine and metabolic pathways. Studies have also explored the involvement of gut microbiota dysbiosis in depression, anxiety, autism, stroke, and pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 164 publications
0
17
0
Order By: Relevance
“…Depression is a major public health concern worldwide affecting numerous people [ 29 ]. The brain-gut-microbiome axis is an important biochemical link between the central nervous system (CNS) and enteric nervous system (ENS) [ 30 ]. The evidence has demonstrated that depression may be related to the gut microbiome [ 11 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is a major public health concern worldwide affecting numerous people [ 29 ]. The brain-gut-microbiome axis is an important biochemical link between the central nervous system (CNS) and enteric nervous system (ENS) [ 30 ]. The evidence has demonstrated that depression may be related to the gut microbiome [ 11 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The brain-gut axis is a bidirectional nodal axis that interacts with the brain and the gastrointestinal tract, which consists of the CNS, autonomic nervous system (ANS), ENS, HPA axis, etc., and the functions of each part are coordinated with each other [ 16 , 30 ]. Intestinal flora changes will cause the host inflammatory response, influence the absorption of nutrients, and change neurotransmitter metabolism and activity in the HPA axis and BDNF levels (lower BDNF levels in the hippocampus are related to depression and anxiety behavior), which will lead to nervous system disorders, such as depression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al [ 83 , 133 ] had stressed the need of integrating large sets of host's multi-omics data and microbial data with machine learning techniques to reveal novel insights into the MGB-axis, independent of existing theories and hypothesis. Kaur et al [ 134 ] also emphasized the role of machine learning in multiomics data analysis to probe MGB relationship and discussed a framework to move beyond prediction to prevention and personalized therapeutics in MGB related disorders.…”
Section: Big Data Analysismentioning
confidence: 99%
“…The bidirectional interaction between the gut microbiota and epigenetics has been documented, although the nature and significance of this relationship has not been fully elucidated. They may act in synchrony to modulate the pathogenesis and progression of NDD ( 94 , 95 ). On the other hand, metabolites produced by the gut microbiota may also reverse some of the previously induced epigenetic modifications ( 96 ) and thereby prevent the development or progression of NDD.…”
Section: Dysbiosis—a Link Between Diet Aging and Nddmentioning
confidence: 99%